Canopy Management of Citrus Trees - Tripti Vashisth; Mongi Zekri; Fernando Alferez (EDIS, 2017)
Tree canopy and bearing volume are two important factors in fruit production and fruit quality; generally, trees with larger canopy volumes produce more fruit than smaller-canopy trees. Therefore, canopy management is an important aspect of citrus production in Florida to avoid problems associated with overcrowding and excessively tall trees. This 3-page document describes canopy management practices for citrus growers. Written by Tripti Vashisth, Mongi Zekri, and Fernando Alferez, and published by the UF/IFAS Horticultural Sciences Department, May 2017.